2007
DOI: 10.1002/jgm.1015
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localisation and pDNA condensation in non‐viral gene delivery

Abstract: Whilst effective levels of non-viral-mediated gene expression generally rely on efficient condensation of pDNA and enhanced interactions with cellular membranes, non-covalently associated NLS within a multi-component non-viral gene vector appears to contribute benefit in sustaining gene expression in non-dividing cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…A number of previous reports have shown that electroporation is an effective method for in vitro gene transfer by direct delivery into the cytoplasm (Zabner et al, 1995;Lechardeur et al, 1999;Collins et al, 2007). We also expected elevation of pDNA intracellular uptake by electroporation prior to increase of nuclear transport.…”
Section: Effect Of Combination Of Plga/pei Nanospheres Nls and Electmentioning
confidence: 64%
See 1 more Smart Citation
“…A number of previous reports have shown that electroporation is an effective method for in vitro gene transfer by direct delivery into the cytoplasm (Zabner et al, 1995;Lechardeur et al, 1999;Collins et al, 2007). We also expected elevation of pDNA intracellular uptake by electroporation prior to increase of nuclear transport.…”
Section: Effect Of Combination Of Plga/pei Nanospheres Nls and Electmentioning
confidence: 64%
“…Therefore, such peptides can serve several roles, such as potential nuclear signaling moieties and the formulation of positively charged pDNA complexes (Conary et al, 1996;Aronsohn and Hughes, 1997;Collins et al, 2007). The modestly up-regulation of pEGFP cellular uptake upon the addition of NF-B p50 analog in the present study was due to an increase in complex attachment to the cell membrane by positively charged amino acids.…”
Section: Effect Of Combination Of Plga/pei Nanospheres Nls and Electmentioning
confidence: 71%
“…Sasaki et al also reported that PEI polyplexes significantly enhanced transgene expression in the liver compared with control mice at 48 h after CCl 4 injection. It was demonstrated that the transfection efficiency of non-viral vectors critically depends on the cell cycle and is enhanced by mitotic activity in the regeneration (Mortimer, 1999;Collins, 2007). Actually, Tada et al reported that partial hepatectomy of mice increased transgene expression of PEI/pDNA complexes in the liver with increased liver weight (Tada, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As seen from Figure Figure 5). Cationic entities such as protamine, 13,18 polylysine, or NLS-containing peptides 19,4 have been widely evaluated for their gene delivery potential and are frequently used to condense and protect plasmid DNA. As seen from the graph, under these conditions, a control cell line MDA-MB-231, expressing basal levels of HER2/3, was not transfected.…”
Section: Her-nls Mediated Uptake Of Dna Into Mda-mb-453 Cells In Vitromentioning
confidence: 99%